BENTUK TINDAK TUTUR DIREKTIF DALAM DIALOG NOVEL LINGKAR TANAH LINGKAR AIR KARYA AHMAD TOHARI: ANALISIS TEORI SEARLE R. JOHN - Ngifat Khoerunnisa; Adina Anisnaeni Rizqina; Muhammad Rohmadi (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study aims to describe the types and functions of directive speech acts based on Searle R. John's theory in Ahmad Tohari's novel Lingkar Tanah Lingkar Air. The research method used is descriptive qualitative method. The technique used is the time triangulation technique to test the validity of the data. The results of this study indicate that there are 46 dialogues in Ahmad Tohari's novel Lingkar Tanah Lingkar Air which are included in directive speech acts. Of the 5 types of speech acts based on Searle R.John's theory, there are 24 dialogues which are included in the type of speech act of ordering, 4 dialogues including speech acts of begging, 6 dialogues including speech acts of suggesting, 9 dialogues including speech acts of advising, and 3 dialogues which includes challenging speech acts. The five types of directive speech acts have different functions depending on the context and speech intonation.